Gyeongju - Lee, Moon-ok; Duverna, Nicholas
Gyeongju』 was published in English version for foreigners. It is a small plate that fits in one hand and is lightly used so that it can be used directly at a travel destination. Opening a small book contains detailed and rich color photographs that support the origin, history, art, and architectural depth and detail of the site. can do. In addition, maps and transportation information are detailed so that first-time visitors can easily find their destinations.Sillas Millennium Altitude Gyeongju is a precious historical city that is hardly found in the world. In particular, many Buddhist ruins are distributed in Gyeongju, so "A Field Guide to History; GYEONGJU has an appendix to explain various statues and hands, and names and forms of towers. In addition to the remains of ancient Shilla designated and preserved as UNESCO World Heritage sites such as Seokguram, Bulguksa and Gyeongju Historical Heritage Sites, the site is divided into 12 natural beauty sites, including Gumpo, Gimsan, Tohamsan, Namsan, Guided tours of Gyeongju with cultural and cultural heritage. In addition to the twelve main courses that make up the main text, the thematic courses are also included in the appendix to help you travel more beautifully.tomado de:https://www.abebooks.com/9788971992883/Gyeongju-Field-Guide-History-Korean-8971992883/plp